Cryobiopsy increases the diagnostic yield of endobronchial biopsy: a multicentre trial - Hetzel, Jürgen; Eberhardt, Ralf; Herth, Felix; Schnabel, Philipp Albert (The European respiratory journal, 2012)
Forceps, brushes or needles are currently the standard tools used during flexible bronchoscopy when diagnosing endobronchial malignancies. The new biopsy technique of cryobiopsy appears to provide better diagnostic samples. The aim of this study was to evaluate cryobiopsy over conventional endobronchial sampling. A total of 600 patients in eight centres with suspected endobronchial tumours were included in a prospective, randomised, single-blinded multicentre study. Patients were randomised to either sampling using forceps or the cryoprobe. After obtaining biopsy samples, a blinded histological evaluation was performed. According to the definitive clinical diagnosis, the diagnostic yield for malignancy was evaluated by a Chi-squared test. A total of 593 patients were randomised, of whom 563 had a final diagnosis of cancer. 281 patients were randomised to receive endobronchial biopsies using forceps and 282 had biopsies performed using a flexible cryoprobe. A definitive diagnosis was achieved in 85.1% of patients randomised to conventional forceps biopsy and 95.0% of patients who underwent cryobiopsy (p<0.001). Importantly, there was no difference in the incidence of significant bleeding. Endobronchial cryobiopsy is a safe technique with superior diagnostic yield in comparison with conventional forceps biopsy.
First published online: Aug 18 2011
Gesehen am 14.06.2018